Bee Venom as a Therapeutic Agent: Effects on Pneumonia and UTI-Causing Bacteria (International Journal of Scientific Research in Science and Technology, 2025)
The aim of this study was to evaluate the antibacterial activity of bee venom as a potential alternative to antibiotics, particularly for treating pneumonia and urinary tract infections (UTIs) caused by antibiotic-resistant and multidrug-resistant bacteria. UTIs can occasionally be caused by some of the same bacteria that usually cause pneumonia, including Klebsiella pneumoniae, Staphylococcus aureus, and Pseudomonas aeruginosa. On the other hand, pneumonia can sometimes result from bacteria such as Serratia rubidaea and Proteus mirabilis, which are mainly responsible for UTIs. Using disk diffusion and minimum inhibitory concentration (MIC) demonstrations, the antibacterial effectiveness of bee venom was assessed for different bacterial strains of pneumonia such as Klebsiella pneumoniae, Staphylococcus aureus, Pseudomonas aeruginosa and Micrococcus luteus as well as UTI causing strains like Serratia rubidaea, Proteus mirabilis and Staphylococcus saprophyticus. According to the results, bee venom significantly inhibited the growth of these infections. This study examines how well bee venom (BV), a natural substance with a complex mix of bioactive chemicals, inhibits the growth of bacteria that cause pneumonia and UTIs. Bee venom’s active ingredients, including melittin, phospholipase A2, and apamin, have been found to have possible roles in its antibacterial properties. The necessity for innovative therapeutic approaches is highlighted by the difficulties faced by traditional antibiotic therapies as a result of growing antimicrobial resistance and MDR. This study emphasizes how bee venom may be used as a substitute treatment for bacteria that cause pneumonia and UTIs.